Coincidence anticipation timing requirements across different stimulus speeds in various sports: A pilot study - Kim, H. (The Sport Journal, 2023)
The ability of coincidence anticipation timing is directly related to athletic performance in sports, and anticipation timing requirements vary according to the sports type. This case study aimed to investigate the coincidence anticipation timing of male university athletes in various sports across different stimulus speeds such as slow (3 mph), moderate (6 mph), and fast (9 mph). Nineteen university athletes from soccer (n = 5), tennis (n = 7), and volleyball (n = 7) participated voluntarily in this study and were compared to non-athletes (n = 6). All participants pressed the button when the light stimulus arrived at the target location of a Bassin anticipation timer to assess anticipation timing accuracy in terms of constant, absolute, and variable errors. A speed effect in constant error (p < 0.001) and a group by speed interaction in variable error (p = 0.044) were found. However, no significant difference was found in absolute error. In conclusion, coincidence anticipation timing requirements are different across sports types. Racket sports such as tennis might be more beneficial to improving anticipation timing skills than other sports or non-athletes.